The effect of Leucaena leucocephala mulch on the growth and yield of irrigated tomato (Lycopersicon esculentus Mill.) - Kafari, Simon A. (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of the Degree of Master of Science in Agroforestry.